تصورات طلبة جامعة البلقاء التطبيقية حول دور الجامعة - العوامله, عبد الله (جامعة الوادي University of Eloued, 2018)
هدفت الدراسة إلى التعرف على دور الجامعة في تنمية الوعي الأمني بمفاهيم الإرهاب والتطرف كما يتصورها طلبة جامعة البلقاء التطبيقية، وفقاً لجنس الطالب، ونوع الكلية، والمستوى الدراسي. تكون أفراد عينة الدراسة من (301) طالباً وطالبة من طلبة الكليات العلمية والإنسانية، ولتحقيق أهداف الدراسة استخدم الباحث استبانة تكونت من ثلاثة محاور تغطي: (مفهوم الإرهاب، مفهوم التطرف، دور الجامعة في تنمية الوعي الأمني). تم التحقق من صدق أداة الدراسة وثباتها. توصلت الدراسة إلى أن الوعي الأمني بمجالي مفهوم الإرهاب، ومفهوم التطرف عند الطلبة جاء بدرجة عالية، بينما جاء مجال دور الجامعة بتنمية الوعي الأمني بدرجة متوسطة، وأظهرت نتائج الدراسة وجود فروق ذات دلالة إحصائية في دور الجامعة في تنمية الوعي الأمني بمفاهيم الإرهاب والتطرف، تبعاً لجنس الطالب في مجال مفهوم التطرف ولصالح الإناث، وفي متغير نوع الكلية في مجال دور الجامعة في التوعية الأمنية، ولصالح طلبة الكليات الإنسانية، وفي متغير المستوى الدراسي في مجال دور الجامعة في التوعية الأمنية ولصالح طلبة السنة الأولى.ABSTRACT:The study aimed at identifying the role of university in the development of security awareness on terrorism and extremism, concepts as perceived by Balqa Applied University students in accordance with gender, college, and academic level. The study sample consisted of(301) male and female students from both scientific and humanities colleges. To achieve the objectives of the study, the researcher used a questionnaire consisted of three domains; the concept of terrorism, the concept of extremism, and the role of the university in developing security awareness. Validity and reliability of the questionnaire used in the study were assessed to support the findings. The findings of the study shows that security awareness in the domain of the concept of terrorism, and the concept of extremism are highly perceived, while the domain of the role of the university in developing security awareness is moderate. The results also show the presence of statistically significant differences in the role of the university in developing the concepts of security awareness on terrorism and extremism. Depending on the role of the university in security awareness, the results shows that the gender is in favor of female students, the college is in favor of humanities colleges and the academic level is in favor of first-year students.
في تنمية الوعي الأمني بمفاهيم الإرهاب والتطرف
مقال
Keywords: الإرهاب، التطرف، الوعي الأمني، دور الجامعة; terrorism; extremism; security awareness; the role of the university